ANALISIS PENGARUH ACTIVITY BASED COSTING TERHADAP KINERJA KEUANGAN DAN KINERJA OPERASIONAL USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) - Sekarsari, Asri; Khairina Nur Izzaty; Firmanto; Widya Pramesti (Journal Of Islamic Economics And Finance, 2021)
The study aims to analyse the impact of the use of Activity Based Costing (ABC) on Micro, Small Medium Enterprises. The population in this study were manufacturing Micro, Small and Medium Enterprises located in Bulukerto District, Wonogiri Regency with a total of 200 manufacturing MSMEs. The sampling technique in this study used probability sampling and random sampling technique. The sample in this study stated 133 manufacturing SMEs in calculating the sample size using Slovin Sampling. The type of data in this study is quantitative, while the data source comes from primary data obtained from the result of the questionnaire. In this study, the data analysis technique used was Partial Least Squares (PLS) 3.0. The result of this indicate that on Activity Based Costing (ABC) variable has a direct effect on operational performance, the Activity Based Costing (ABC) variable has a direct effect on financial performance, the operational performance variable has a direct effect on financial performance, Activity Based Costing (ABC) on financial performance through operational performance has a direct effect, this effect can be seen in the original sample which shows positive result, the T-statistic and P-values shows significant result. In the mediation test, Activity Based Costing (ABC) through operational performance has no effect on financial performance, because in direct and indirect relationship it has the same result, namely positive and significant. So in the mediation test, the presence or absence of operational performance variables doest not affect Activity Based Costing (ABC) on financial performance.